2021
DOI: 10.21873/anticanres.14915
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Survival Score for Patients With Anaplastic Thyroid Carcinoma: A Retrospective Study from a Regional Registry

Abstract: Background/Aim: Anaplastic thyroid carcinoma (ATC) is the least common but most lethal of thyroid cancer, despite various therapeutic options, with limited efficacy. In order to help therapeutic decision-making, the purpose of this study was to develop a new prognostic score providing survival estimates in patients with ATC. Patients and Methods: Based on a multivariate analysis of 149 retrospectively analyzed patients diagnosed with ATC from 1968 to 2017 at a referral center, a propensity score was developed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…A possible explanation for that may lie in that the extremely short survival of ATC patients leads to the statistical insignificance of lymph node invasion for survival. Similarly, no association of tumor size with survival was found in our study, in line with a small study ( 16 ) but contrary to two previous studies presenting a negative correlation of tumor size with survival ( 14 , 27 ). This discrepancy could be attributed to inadequate confounding factors controlled and small sample size.…”
Section: Discussionsupporting
confidence: 79%
“…A possible explanation for that may lie in that the extremely short survival of ATC patients leads to the statistical insignificance of lymph node invasion for survival. Similarly, no association of tumor size with survival was found in our study, in line with a small study ( 16 ) but contrary to two previous studies presenting a negative correlation of tumor size with survival ( 14 , 27 ). This discrepancy could be attributed to inadequate confounding factors controlled and small sample size.…”
Section: Discussionsupporting
confidence: 79%
“…With the progression of the disease, TC in patients' body has different forms, including papillary TC, follicular thyroid carcinoma TC, and medullary TC. At present, the common clinical carcinogenesis is mostly papillary [ 2 ]. In clinical practice, surgical resection and lymph node dissection are mostly performed for TC, but the traditional surgical method brings large wounds to the body surface of TC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The data for the above study were obtained from the SEER database. Meanwhile, a retrospective Study from Regional Registry studied 149 patients with ATC showed that age, tumor size, distant metastasis status were independent variables, definitely affecting survival rate of ATC, as analyzed by multivariable Cox proportional hazard regression [ 27 ]. Traditional Cox regression is the most convenient way to solve most survival prediction problems because its results are easy to interpret.…”
Section: Discussionmentioning
confidence: 99%